2008
DOI: 10.1002/ijc.23735
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of repression by modified p53 on the PDGF β‐receptor promoter

Abstract: Herein, we show that both exogenously transfected and endogenously activated p53 repress promoter activity and expression of PDGFRB. p53 binds the proximal promoter containing the CCAAT motif as examined by EMSA and chromatin immunoprecipitation. However, gradual induction of p53 in tet-onSAOS2 cells resulted in a transient increase of the PDGFRB-promoter activity and its expression. As binding of p53 to the promoter increased, previously bound p73, DNp73, c-Myc, HDAC1 and HDAC4 were dismissed from the repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…We demonstrated that increased binding of p53 to the proximal Pdgfr␤ promoter (but not the distal promoter or intron) was evident when Arf was expressed ectopically in 10T1/2 cells (Widau and Skapek, unpublished data). This is in agreement with a report by Yang and colleagues revealing a putative p53-binding element in the proximal Pdgfr␤ promoter in mitomycin C (MMC)-treated MEFs (63). However, we were not able to detect p53 binding to the Pdgfr␤ promoter in wild-type MEFs with or without endogenous p19…”
Section: Arf Controls Pdgfr␤-driven Proliferation In Vivo the Hyperpsupporting
confidence: 93%
See 4 more Smart Citations
“…We demonstrated that increased binding of p53 to the proximal Pdgfr␤ promoter (but not the distal promoter or intron) was evident when Arf was expressed ectopically in 10T1/2 cells (Widau and Skapek, unpublished data). This is in agreement with a report by Yang and colleagues revealing a putative p53-binding element in the proximal Pdgfr␤ promoter in mitomycin C (MMC)-treated MEFs (63). However, we were not able to detect p53 binding to the Pdgfr␤ promoter in wild-type MEFs with or without endogenous p19…”
Section: Arf Controls Pdgfr␤-driven Proliferation In Vivo the Hyperpsupporting
confidence: 93%
“…The findings generally support the concept that p53 activated by genotoxic exposure to mitomycin C represses the Pdgfr␤ promoter in MEFs by recruiting histone deacetylases 1 and 4 (63). Defining a role for p53 is further complicated by the choreographed changes in the binding of various isoforms of the p53-related p73 protein, which can also influence this promoter (13).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations